MORPHO-HISTOLOGICAL CHARACTERISTICS OF BRUISES WITH DIFFERENT AGE - QUALITATIVE STUDY - Kostadinova Petrova, Irena; Mitevska, Elida; Kakasheva Mazhenkoska, Lena; Tasheva, Ljubica; Stojkovska, Natasha; Janeska, Biljana (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Bruises are common skin lesions that occur as the force hits the skin, but integrity of the skin is not impaired. Their significance is important in forensic expert reports in determining the time of death in many cases of domestic violence or child abuse. The aim of this study was to present the differences between bruises with different time of origin by evaluation of their morpho-histological characteristics.  The study included 60 human skin samples divided into control and experimental groups A, B, C, D. The experimental group A included bruised human skin samples with <1day old bruises, experimental group B included bruised human skin samples with 1-3 days old bruises, experimental group C included bruised human skin samples with 3-7 days old bruises and experimental group D included bruised human skin samples with 7-14 days old bruises. Paraffin sections of the skin were stained with Hematoxylin-eosin, Giemsa, Perlâ€™s Prussian Blue, Masson-Goldner methods of staining and application of anti-HO-1 antibody. All paraffin sections were evaluated by light microscopy and photodocumented. Our results have shown changes in color in bruises with different age due to infiltration with different immune cells and metabolism of extracellular hemoglobin.  Granulocyte infiltration is seen shortly after the initiation of the bruise, while after few days of initiation, usually 1-3, there is macrophage infiltration in the field of bleeding. Presence of macrophages in the field of bleeding increases as bruises age. These histological characteristics appear in direction of healing the bruise, together with phagocytosis of the erythrocytes and removing the tissue debris.  Keywords : bruises, time of origin, morpho-histological characteristics, microscopic analysis